Bacilli-Mediated Degradation of Xenobiotic Compounds and Heavy Metals - Arora, Pankaj Kumar (Frontiers in Bioengineering and Biotechnology, 2020)
Xenobiotic compounds are man-made compounds and widely used in dyes, drugs, pesticides, herbicides, insecticides, explosives, petroleum products, and other industrial chemicals. These compounds have been released into our soil and water due to anthropogenic activities and improper waste practice and cause serious damage to aquatic and terrestrial ecosystems due to their toxic nature. The United States Environmental Protection Agency (USEPA) listed several toxic substances as priority pollutants. Bacterial remediation is identified as an emerging technique to remove these substances from the environment. Many bacterial genera are actively involved in the degradation of toxic substances. Among the bacterial genera, the members of the genus Bacillus have a great potential to degrade or transform various toxic substances. Many Bacilli have been isolated and characterized by their ability to degrade or transform a wide range of compounds including both naturally occurring substances and xenobiotic compounds. This review describes the biodegradation potentials of Bacilli towards various toxic substances, including 4-chloro-2-nitrophenol, insecticides, pesticides, herbicides, explosives, drugs, polycyclic aromatic compounds, heavy metals, azo dyes, and aromatic acids. Besides, the advanced technologies used for bioremediation of environmental pollutants using Bacilli are also briefly described. This review will increase our understanding of Bacilli-mediated degradation of xenobiotic compounds and heavy metals.